The impact of diversification and credit risk on commercial banks’ stock prices: empirical evidence from the GCC countries (Economic studies journal, 2023)
This study aimed to measure the impact of diversification and credit risk on the stock prices of commercial banks for a sample of 58 commercial banks listed in the stock exchanges operating in the Gulf Cooperation Council countries, and for balanced annual data during the time period (2011-2018), the experimental part of the study was based on Multiple linear regression analysis of the panel data, based on the corrected standard error estimation (PCSE) method.The results showed that the diversification coefficient has a positive and statistically significant effect on the stock prices of commercial banks, while the results showed that the credit risk coefficient has a negative and statistically significant effect on the share prices of commercial banks. In addition, the study found evidence that bank size has a significant positive effect on stock prices of commercial banks. Based on this and its findings, the study recommends that bank officials highlight the increased interest in diversifying income due to its importance in improving the banking sector, and recommends that investors take into account the subtle factors affecting prices to make the right decision about their investments.
Keywords: Diversification; Commercial Banks; Credit Risk; Stock Prices